Dielectric and electrical properties of La@NiO SNPs for high-performance optoelectronic applications. Issue 11 (1st June 2021) - Shkir, Mohd; Khan, Aslam; Chandekar, Kamlesh V.; Sayed, M.A.; El-Toni, Ahmed Mohamed; Ansari, Anees A.; Adil, Syed F.; Ghaithan, Hamid; Algarni, H.; AlFaify, S.
Abstract: A successful flash combustion synthesis of NiO spherical nanoparticles with various contents of lanthanum (La) doping (La@NiO SNPs) with remarkably enhanced dielectric and electrical properties are reported. Single phase has been confirmed through X-ray diffraction and FT-Raman spectroscopic analysis. Increasing La content in NiO reduced the crystallite size by 341% to 6.65 nm from 22.70 nm. The composition of elements in the final product was assessed via EDX analysis. Moreover, monophasic La@NiO SNPs synthesis with size reduction was observed using field emission scanning electron microscopy (FESEM). A red shift in optical energy gaps (3.52–3.26 eV) was observed with increasing La contents from pure to 10 wt%. Capacitance (109–964 PF), impedance (9.41 × 10 4 –1.67 × 10 4  kΩ), dielectric constant (100–967), dielectric loss (335–10666), and electrical conductivity (4–5 S/m) values were remarkably improved with La doping. The current (I)–voltage (V) characteristics of pure and La@NiO NPs were performed under the biased voltage of ±20 V. Current was noticed in the range of (3.81 × 10 −4 –9.91 × 10 −3 amp) at pure, 1.0, 3.0, 5.0, and 10 wt% of La@NiO NPs. Enhancements in the dielectric and electrical properties of as-synthesized NPs make them suitable for optoelectronics uses.